2017
DOI: 10.7554/elife.26243
|View full text |Cite
|
Sign up to set email alerts
|

A vitamin-B2-sensing mechanism that regulates gut protease activity to impact animal’s food behavior and growth

Abstract: To survive challenging environments, animals acquired the ability to evaluate food quality in the intestine and respond to nutrient deficiencies with changes in food-response behavior, metabolism and development. However, the regulatory mechanisms underlying intestinal sensing of specific nutrients, especially micronutrients such as vitamins, and the connections to downstream physiological responses in animals remain underexplored. We have established a system to analyze the intestinal response to vitamin B2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 52 publications
3
64
0
Order By: Relevance
“…A Bacterial Mutant Screen Identifies the Benefit of E. Coli-Produced Ent to Host Development We created a unique assay to facilitate the identification of microbial metabolites that benefit growth and development of host animals. Our previous studies revealed that heat-killed (HK) E. coli lacks certain molecules that are collectively required for C. elegans larval growth (Qi et al, 2017). Larval growth was recovered when the heat-killed E. coli plate was supplemented with a trace amount of live E. coli, which alone could not support worm growth ( Figure 1A), suggesting that the trace amount of live bacteria generated metabolites that rendered the heat-killed food usable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Bacterial Mutant Screen Identifies the Benefit of E. Coli-Produced Ent to Host Development We created a unique assay to facilitate the identification of microbial metabolites that benefit growth and development of host animals. Our previous studies revealed that heat-killed (HK) E. coli lacks certain molecules that are collectively required for C. elegans larval growth (Qi et al, 2017). Larval growth was recovered when the heat-killed E. coli plate was supplemented with a trace amount of live E. coli, which alone could not support worm growth ( Figure 1A), suggesting that the trace amount of live bacteria generated metabolites that rendered the heat-killed food usable.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that the nematode C. elegans is an excellent system to study functions of bacterial metabolites on animal physiology (e.g., Garcia-Gonzalez et al, 2017;Gusarov et al, 2013;Han et al, 2017;Meisel et al, 2014;Samuel et al, 2016;Scott et al, 2017). We have previously developed a unique assay system to evaluate the impact of microbiota-produced metabolites on animal development and behaviors, which led to the identification of an intestinal pathway that regulates animal food behaviors in response to deficiency of bacteria-produced vitamin B2 (Qi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin B2 (Riboflavin) is required for animals to progress through L1. B2 promotes intestinal protease expression and activity that likely promotes digestion . In this context, B2 may be required for the absorption of many nutrients, and its absence may induce a starvation state.…”
Section: Nutrient and Metabolic Information Is Integrated Into Signalmentioning
confidence: 99%
“…The authors take advantage of the ability of C. elegans to grow and develop normally on agar plates seeded with live, but not heat-killed, Escherichia coli. Previously, the authors used this experimental system to define a requirement of C. elegans for vitamin B2, riboflavin (Qi et al, 2017). And Watson et al (2014) had conducted a systemslevel metabolic investigation of the differential growth rates of C. elegans on different bacterial species to identify a benefit of vitamin B12 on growth and development of C. elegans.…”
mentioning
confidence: 99%